A retrospective case-series of influence of chronic hepatitis B on synchronous liver metastasis of colorectal cancer - Zhu, Lin; Gong, Piqing; Liu, Ye; Shi, Yunjie; Wang, Wenqiang; Zhang, Wei; Hu, Zhiqian; Li, Xinxing (Frontiers in Oncology, 2023)
Objectives: This study aimed to investigate the effect of HBV on the occurrence of synchronous liver metastases (SLM) of colorectal cancer (CRC). Methods: Univariate and multivariate analyses were used to analyze the influence of clinical parameters on the occurrence of SLM. Results: A total of 6, 020 patients with primary CRC were included in our study, of which 449 patients carrying HBsAg(+) accounted for 7.46%. 44 cases of SLM occurred in the HBsAg(+) group, accounting for 9.80%, which was much lower than 13.6% (758/5571) in the HBsAg(-) group (X=5.214, P=0.022). Among CRC patients with HBsAg(-), the incidence of SLM was 24.9% and 14.9% in the group with high APRI and FIB-4 levels, respectively, which were significantly higher than that in the compared groups (12.3% and 12.5%, all P<0.05). Compared with the control group, female patients, late-onset patients, and HBV-infective patients had lower risks of SLM (HR=0.737, 95%CI: 0.614-0.883, P<0.001; HR=0.752, 95%CI: 0.603-0.943, P=0.013; HR=0.682, 95%CI: 0.473-0.961, P=0.034). Conclusions: The carriage of HBsAg(+) status inhibited the occurrence of SLM from CRC. HBV-causing liver cirrhosis did not further influence the occurrence of SLM, whereas non-HBV-factor cirrhosis promoted the occurrence of SLM. Nevertheless, this still required prospective data validation.